Brown fat is essential for cold-induced thermogenesis but not for obesity resistance in aP2-Ucp mice - Stefl, B; Janovská, A; Hodný, Z; Rossmeisl, M; Horáková, M; Syrový, I; Bémová, J; Bendlová, B; Kopecký, J (The American journal of physiology, 1998)
The role of brown adipose tissue in total energy balance and cold-induced thermogenesis was studied. Mice expressing mitochondrial uncoupling protein 1 (UCP-1) from the fat-specific aP2 gene promoter (heterozygous and homozygous aP2-Ucp transgenic mice) and their nontransgenic C57BL6/J littermates were used. The transgenic animals are resistant to obesity induced by a high-fat diet, presumably due to ectopic synthesis of UCP-1 in white fat. These animals exhibited atrophy of brown adipose tissue, as indicated by smaller size of brown fat and reduction of its total UCP-1 and DNA contents. Norepinephrine-induced respiration (measured in pentobarbital sodium-anesthetized animals) was decreased proportionally to the dosage of the transgene, and the homozygous (but not heterozygous) transgenic mice exhibited a reduction in their capacity to maintain body temperature in the cold. Our results indicate that the role of brown fat in cold-induced thermogenesis cannot be substituted by increased energy expenditure in other tissues.
Keywords: obezita; membránové transportní proteiny; Uncoupling Protein 1; tuková tkáň; Immunity, Innate; Membrane Proteins; Promoter Regions, Genetic; proteiny; Mice, Transgenic; iontové kanály; Homozygote; Proteins; Transgenes; Thyroid Gland; nízká teplota; myši transgenní; Uncoupling Protein 2; Membrane Transport Proteins; zvířata; Mitochondrial Proteins; myši; transgeny; mitochondriální proteiny; myši inbrední C57BL; štítná žláza; Cold Temperature; Mice; transportní proteiny; hnědá tuková tkáň; homozygot; uncoupling protein 1; Carrier Proteins; Energy Metabolism; energetický metabolismus; Male; Adipose Tissue; Body Temperature Regulation; promotorové oblasti (genetika); Mice, Inbred C57BL; uncoupling protein 2; membránové proteiny; Ion Channels; Obesity; Body Weight; Animals; tělesná hmotnost; mužské pohlaví; Adipose Tissue, Brown; přirozená imunita; termoregulace